If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5b + -6 + -10b + -5 = 0 Reorder the terms: -6 + -5 + 5b + -10b = 0 Combine like terms: -6 + -5 = -11 -11 + 5b + -10b = 0 Combine like terms: 5b + -10b = -5b -11 + -5b = 0 Solving -11 + -5b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + -5b = 0 + 11 Combine like terms: -11 + 11 = 0 0 + -5b = 0 + 11 -5b = 0 + 11 Combine like terms: 0 + 11 = 11 -5b = 11 Divide each side by '-5'. b = -2.2 Simplifying b = -2.2
| 10x-31+15=0 | | 2t^2%-3 | | 18x+28=180 | | 8b^5+b^2-b^3-2b^5-4b^2= | | 5a-5+8=13 | | 5x+2-7x=8 | | 34/5/z | | 2(a+12)=20 | | 6x-1+3x-8=90 | | f=a+b+c/3 | | 2a+12=32 | | 78y-44y= | | lx-1l=3 | | 54.313*12.09= | | 1+44y-44y= | | 3a+2c-5= | | 4(x+1/4)=16 | | 5b+2a+4= | | -2k+28=21k+49 | | n=70 | | -9x-6=x-30 | | y=x+y/2 | | 7x+7=18x-4 | | 0=(.2-x)*(.0002-3x)*(.0002-3x)*(.0002-3x) | | x=3+0.25y | | x=3+0.25y | | 3(15)+5=5(15)-25 | | -1/3=5 | | e/6=12/4 | | 12/4=d/8 | | (z+8)(z-11)= | | -9(x-9)=(x+63) |